2005
DOI: 10.1042/bj20050214
|View full text |Cite
|
Sign up to set email alerts
|

Highly conserved proximal promoter element harbouring paired Sox9-binding sites contributes to the tissue- and developmental stage-specific activity of the matrilin-1 gene

Abstract: The matrilin-1 gene has the unique feature that it is expressed in chondrocytes in a developmental stage-specific manner. Previously, we found that the chicken matrilin-1 long promoter with or without the intronic enhancer and the short promoter with the intronic enhancer restricted the transgene expression to the columnar proliferative chondroblasts and prehypertrophic chondrocytes of growth-plate cartilage in transgenic mice. To study whether the short promoter shared by these transgenes harbours cartilage-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 52 publications
(113 reference statements)
5
54
0
10
Order By: Relevance
“…Matrilin 1 is expressed in chondrocytes in a developmental stage-specific manner in vertebrates. 32,33 Treatment with TDCPP significantly increased the expression of matrilin 1 precursor, suggesting disruption in chondrogenesis. Collectedly, we speculated that larval malformation (trunk curvature) resulted from abnormal development of somites, fast muscle, and cartilage after TDCPP exposure.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Matrilin 1 is expressed in chondrocytes in a developmental stage-specific manner in vertebrates. 32,33 Treatment with TDCPP significantly increased the expression of matrilin 1 precursor, suggesting disruption in chondrogenesis. Collectedly, we speculated that larval malformation (trunk curvature) resulted from abnormal development of somites, fast muscle, and cartilage after TDCPP exposure.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Specific in vitro and in vivo studies have revealed that the SRY (sex-determining region Y)-box 9 (SOX9) transcription factor binds to consensus sequence pairs in the upstream region of the COL2A1 and COL9A1 genes and regulates expression (10)(11)(12)(13)(14)(15)(16). SOX9 is a protein of the HMG-box DNA-binding protein class, which recognize the CCTTGAG sequence.…”
Section: Introductionmentioning
confidence: 99%
“…A Sox9 az E csoport tagjaként rendelkezik transzaktivációs doménnel, transzkripciós faktorként direkt szerepe van több porc mátrix fehérjét kódoló gén, többek között a matrilin-1 gén szabályozásában is [80].…”
Section: A Transzkripciós Szabályozásban Résztvevı Fontosabb Fehérje unclassified
“…A rövid (-334/+67), illetve a teljes hosszúságú (-2011/+67) matrilin-1 promoter által irányított luciferáz riporter gént tartalmazó konstrukciók (FO15Luc és AC8Luc) már rendelkezésünkre álltak [80].…”
Section: Tranziens Expressziós Kísérletekhez Használt Plazmidok Készíunclassified
See 1 more Smart Citation